Batch Experiments Demonstrating a Two-Stage Bacterial Process Coupling Methanotrophic and Heterotrophic Bacteria for 1-Alkene Production From Methane - Khanongnuch, Ramita; Mangayil, Rahul; Santala, Ville; Hestnes, Anne Grethe; Svenning, Mette Marianne; Rissanen, Antti J. (Frontiers in Microbiology, 2022)
Methane (CH4) is a sustainable carbon feedstock for value-added chemical production in aerobic CH4-oxidizing bacteria (methanotrophs). Under substrate-limited (e.g., oxygen and nitrogen) conditions, CH4 oxidation results in the production of various short-chain organic acids and platform chemicals. These CH4-derived products could be broadened by utilizing them as feedstocks for heterotrophic bacteria. As a proof-of-concept, a two-stage system for CH4 abatement and 1-alkene production was developed in this study. Type I and Type II methanotrophs, Methylobacter tundripaludum SV96 and Methylocystis rosea SV97, respectively, were investigated in batch tests under different CH4 and air supplementation schemes. CH4 oxidation under either microaerobic or aerobic conditions induced the production of formate, acetate, succinate, and malate in M. tundripaludum SV96, accounting for 4.8–7.0% of consumed carbon from CH4 (C-CH4), while M. rosea SV97 produced the same compounds except for malate, and with lower efficiency than M. tundripaludum SV96, accounting for 0.7–1.8% of consumed C-CH4. For the first time, this study demonstrated the use of organic acid-rich spent media of methanotrophs cultivating engineered Acinetobacter baylyi ADP1 ‘tesA-undA cells for 1-alkene production. The highest yield of 1-undecene was obtained from the spent medium of M. tundripaludum SV96 at 68.9 ± 11.6 µmol mol Csubstrate-1. However, further large-scale studies on fermenters and their optimization are required to increase the production yields of organic acids in methanotrophs.